2020
DOI: 10.1002/tea.21650
|View full text |Cite
|
Sign up to set email alerts
|

Sketching, not representational competence, predicts improved science learning

Abstract: Representational competence is a target of novel learning environments given the assumption that improved representational competence improves learning in science. There exists little evidence, however, that improving representational competence is positively correlated with learning outcomes across science disciplines. In this report, we argue that the previously reported weak relationships between representational competence and science learning outcomes have resulted from designs that do not explicitly anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 40 publications
2
26
0
Order By: Relevance
“…10,22,23 The term representational competence describes an ability to understand chemical phenomena and translate the phenomena from one representation to other, for example, connecting macroscopic to symbolic and or submicroscopic and vice versa, drawing and predicting chemical reactions phenomena. 22,24,25 The contribution of this competence towards students' success in science learning has been of concern in many areas 26,27 including science, technology, engineering, and math (STEM), 28 and physics. 29 This competence has also been considered as an essential factor to be improved in all educational levels.…”
Section: Introductionmentioning
confidence: 99%
“…10,22,23 The term representational competence describes an ability to understand chemical phenomena and translate the phenomena from one representation to other, for example, connecting macroscopic to symbolic and or submicroscopic and vice versa, drawing and predicting chemical reactions phenomena. 22,24,25 The contribution of this competence towards students' success in science learning has been of concern in many areas 26,27 including science, technology, engineering, and math (STEM), 28 and physics. 29 This competence has also been considered as an essential factor to be improved in all educational levels.…”
Section: Introductionmentioning
confidence: 99%
“…A study shows that communication skills consistently fail to be demonstrated by science students than analytical, technical, and problemsolving skills (Gray, 2005;Sari & El Islami, 2020;Stieff & DeSutter, 2021). Graduates do not consistently display communication skills when hiring (McInnis et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, Nitz et al (2014) results suggest a negative gain relationship between students generating representations and building conceptual knowledge [20], which refutes earlier stud-ies (e.g., [21,22]). Apparent is the lack of a conclusive understanding of how student-generated representations impact students' science conceptual and technical learning [23][24][25][26]. Due to this lack of clarity, in this study we treat development of graph generation RC as an individual component of learning to "think like a physicist", distinguishable from learning other RC components or scientific concepts [20].…”
Section: A Generating Representations: a Component Of Representational Competencymentioning
confidence: 99%